Early Brain Volume Changes After Stroke: Subgroup Analysis From the AXIS-2 Trial - Bu, Ning; Churilov, Leonid; Khlif, Mohamed Salah; Lemmens, Robin; Wouters, Anke; Fiebach, Jochen B.; Chamorro, Angel; Ringelstein, E. Bernd; Norrving, Bo; Laage, Rico; Grond, Martin; Wilms, Guido; et al. (Frontiers in Neurology, 2022)
Background and Purpose The evolution of total brain volume early after stroke is not well understood. We investigated the associations between age and imaging features and brain volume change in the first month after stroke. Methods We retrospectively studied patients with acute ischemic stroke enrolled in the AXIS-2 trial. Total brain volume change from hyperacute MRI data to the first month after stroke was assessed using unified segmentation in SPM12. We hypothesized that age, ischemic brain lesion size, and white matter (WM) changes were associated with larger brain volume change. Enlarged perivascular spaces (EPVSs) and white matter hyperintensities (WMHs) were rated visually and the presence of lacunes was assessed. Results We enrolled 173 patients with a mean age of 67 ± 11 years, 44% were women. There was a median 6 ml decrease in volume (25th percentile −1 ml to 75th percentile 21 ml) over time, equivalent to a median 0.5% (interquartile range [IQR], −0.07%−1.4%), decrease in brain volume. Age was associated with larger brain volume loss (per 10 years of age, 5 ml 95% CI 2–8 ml). Baseline diffusion weighted imaging (DWI) lesion volume was not associated with greater volume loss per 10 ml of lesion volume, change by 0 ml (95% CI −0.1 to 0.1 ml). Increasing Fazekas scores of deep WMH were associated with greater tissue loss (5 ml, 95% CI 1–10 ml). Conclusions Total brain volume changes in a heterogenous fashion after stroke. Volume loss occurs over 1 month after stroke and is associated with age and deep WM disease. We did not find evidence that more severe strokes lead to increased early tissue loss.